RESULTS OF 192IR CONTACT RADIATION THERAPY FOR CERVIX UTERI CANCER - O. A. Kravets; L. A. Maryina; M. I. Nechushkin; Yu. V. Andreyeva; N. A. Pirogova (ABV-press, 2014)
The paper presents the results of treatment for locally advanced cervix uteri cancer, by applying a 192Ir radioactive source for contact radiation. Three- and five-year overall and relapse-free survival rates have been obtained for stages: 82.5 and 82.5%; 78.4 and 78.4% for Stage IIb; 57 and 52.3%; 41.6 and 41.6 for IIIb; 53.3 and 47.3%; 42.4 and 37.7% for IVb, respectively.